55.0k views
4 votes
Use substitution to solve the following system of linear equations and fill in the following blanks:

x + y + z = -6
x - 6y - 7z = -29
-7y - 5z = 4
In the first step, select Equation 1 and find an expression for variable X in terms of other variables:
x = - y -z - 6
Then substitute X in Equation 2. The result is the following new equation:
___y+___ z = -23
In the last step, using back-substitution, the solution for this system is:
x=
y=
Z=

User Vishrant
by
4.9k points

1 Answer

4 votes

Answer:


x=-4


y=3


z=-5

Explanation:

Given:


x+y+z=-6


x-6y-7z=-29


-7y-5z=4

Solve for
x in the 1st equation:


x+y+z=-6


x+y=-z-6


x=-y-z-6

Substitute the value of
x into the 2nd equation and solve for
z:


x-6y-7z=-29


(-y-z-6)-6y-7=-29


-7y-z-13=-29


-7y-z=-16


-z=-16+7y


z=16-7y

Substitute the value of
z into the 3rd equation and solve for
y:


-7y-5z=4


-7y-5(16-7y)=4


-7y-80+35y=4


28y-80=4


28y=84


y=3

Plug
y=3 into the solved expression for
z and evaluate to solve for
z:


z=16-7(3)


z=16-21


z=-5

Plug
z=-5 into the solved expression for
x and evaluate to solve for
x:


x=-(3)-(-5)-6


x=-3+5-6


x=2-6


x=-4

Therefore:


x=-4


y=3


z=-5

User Tomas Mikula
by
5.0k points